Peran Motivasi Memasuki dunia Kerja dalam memediasi pengaruh Pengalaman Praktik Kerja Industri dan Locus of Control Internal terhadap Kesiapan Kerja Siswa - Armiati, Armiati; Zahmelinda, Septia; Hidayat, M Topit (Jurnal Ecogen, 2024)
This study aims to determine the effect of  internship  experience, internal locus of control, and motivation as a mediating variable on the work readiness of SMKN 2 Pariaman students. This type of research is causative. The research population was all class students of SMKN 2 Pariaman and the determination of the number of samples using the slovin formula was 153 samples. The sampling technique used proportional random sampling technique. The data used is the type of primary data obtained through the distribution of questionnaires to students. The analytical method used is path analysis using SPSS.The results showed that  internship experience did not significantly affect the motivation of SMKN 2 Pariaman students, internal locus of control had a significant effect on the motivation,  internship experience had a significant effect on students' work readiness, internal locus of control has a significant effect on student work readiness, motivation does not significantly affect student work readiness, industrial work experience does not significantly affect student work readiness through motivation as a mediating variable, internal locus of control has no significant effect on student work readiness as a mediating variable.